2011
DOI: 10.1088/0022-3727/44/17/174021
|View full text |Cite
|
Sign up to set email alerts
|

Controlling roughness: from etching to nanotexturing and plasma-directed organization on organic and inorganic materials

Abstract: We describe how plasma-wall interactions in etching plasmas lead to either random roughening / nanotexturing of polymeric and Silicon surfaces, or formation of organized nanostructures on such surfaces. We conduct carefully designed experiments of plasma-wall interactions to understand the causes of both phenomena, and present Monte-Carlo simulation results confirming the experiments. We discuss emerging applications in wetting and optical property control, protein adsorption, microfluidics and lab-on-a-chip f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 64 publications
(58 reference statements)
3
96
0
2
Order By: Relevance
“…According to Wenzel's equation 48 , increasing the roughness of a surface enhances the wettability due to the chemistry of the surface. In our case, the increase in the roughness due to the plasma treatment 49 was further enhanced by the random deposition of PVA 50 . These two combined effects account for the long-lasting hydrophilic effect on the PDMS surfaces (430 days).…”
Section: Discussionmentioning
confidence: 52%
“…According to Wenzel's equation 48 , increasing the roughness of a surface enhances the wettability due to the chemistry of the surface. In our case, the increase in the roughness due to the plasma treatment 49 was further enhanced by the random deposition of PVA 50 . These two combined effects account for the long-lasting hydrophilic effect on the PDMS surfaces (430 days).…”
Section: Discussionmentioning
confidence: 52%
“…36 Furthermore, stochastic roughness (or texturing) in micro-channels can be harnessed for multi-functional properties like anti-reflectivity and optical transparency. 33 Recent work has shown that this roughness can be "tailored" by tuning the fabrication process 4,34 and open up promising avenues to enhance microfluidic applications. These promising developments necessitate a thorough understanding of the flow characteristics of fluids in rough microchannels and has been the focus of recent studies.…”
mentioning
confidence: 99%
“…Biological properties can be controlled and modified via the intrinsic ability of plasma to modify surface properties of polymers, like surface chemistry, ζ-potential, wettability, electrical conductivity and morphology [159][160][161] [162].…”
Section: Post Treatment By Plasma Modificationmentioning
confidence: 99%
“…Another advantage is the fact that it can change selectively areas of interest and not the whole area of the scaffold comparing to all the other methods, giving this method the option to create multifunctional scaffolds using one tool. Plasma in principle creates chemical modification by introducing energetic ions on the surface and subsequently changes conductivity and surface energy [161]. As in section 4.2.1 it can be used as a different kind of chemical modification method for biomolecule immobilization and this way improving cell adhesion, proliferation, and viability [163].…”
Section: Post Treatment By Plasma Modificationmentioning
confidence: 99%
See 1 more Smart Citation